Historical aspects of arm wrestling development in the system of power sports - Markin E.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to analyze the main historical aspects of the emergence and development of training and competitive processes in arm wrestling. Methods and structure of the study. Scientific work is organized in accordance with the norms and rules for preparing and conducting descriptive research using the method of document analysis. Results and conclusions. Many of the most important aspects of the history, theory, and methodology of arm wrestling remain poorly researched or at least not reflected on the pages of scientific publications. In our opinion, the presentation of arm wrestling as a socio-pedagogical system would help to eliminate, if not all, then most of the numerous gaps. In modern practice of Russian sports, the socio-pedagogical system of strength sports is brought into line with the specific social context